Some important combinations of detection techniques for electrophoresis in capillaries and on chips with emphasis on electrochemical principles - Opekar, František; Stulík, Karel (Electrophoresis, 2011)
Analyses of very complex samples involving capillary and chip electrophoresis often require dual (multiple) detection to attain sufficient selectivity of determination. The present work reviews and critically evaluates selected combinations of electrochemical detection techniques among themselves and with absorption spectrometric, fluorescence and luminescence techniques. Amperometry, contact and contactless conductometry, UV photometry and fluorescence measurements are paid special attention. Some information is also given on combinations of spectrometric techniques with mass spectrometry. The properties of the detection systems are critically discussed, examples are illustrated in figures and some details on the characteristics of dual detectors and their applications are tabulated.
Keywords: elektroforéza kapilární; elektroforéza mikročipová; Electrophoresis, Microchip; hmotnostní spektrometrie; organické látky; Organic Chemicals; Mass Spectrometry; Electrophoresis, Capillary